The Relationship Between Multiparous Pregnant Women's Knowledge of Effleurage Massage and Back Pain in Pregnant Women in the Third Trimester at the Polyclinic RS. Bhayangkara Indramayu - Novrida Ashar, Irda; Eka Stia Murni, Dewi; Nurbaeti , Esy (Ann Publisher, 2024)
One of the most frequently reported complaints among pregnant women in the third trimester is back pain. The intensity of the pain fluctuates, ranging from 50% to 70%, and it is one of the contributing factors to the prevalence of cesarean deliveries. The objective of this investigation is to ascertain the correlation between the knowledge of multi-para pregnant women regarding effleurage massage and back pain in pregnant women in the third trimester at the Hospital Polyclinic. Bhayangkara Indramayu. A correlational investigation with a cross-sectional research design was implemented. The study population consists of all multi-pregnant women in the third trimester who encountered back pain at the Hospital Polyclinic.In September 2023, Bhayangkara Indramayu was born. The total number of individuals with a sample of 32 respondents was 32. The chi-square test is the data analysis instrument employed. The results of this study were obtained by 22 (68.8%) respondents with adequate knowledge, 10 (31.3%) respondents with poor knowledge, 4 (12.5%) respondents with no pain, 16 (50%) respondents with mild pain, 10 (31.3%) respondents with moderate pain, and 2 (6.3%) respondents with severe pain. The p-value of the analysis results was 0.005, indicating a correlation between the knowledge of multi-para pregnant women about effleurage massage and back discomfort in pregnant women in the third trimester at the Hospital Polyclinic. Bhayangkara Indramayu. It is recommended that the subsequent researcher expand this research by increasing the number of samples and variables.